A Modern View on the Treatment for Acute Calcium Channel Blocker Poisoning - A. Yu. Simonova; K. K. Ilyashenko; M. M. Potskhveriya; M. V. Belova; L. R. Asanova (Неотложная медицинская помощь, 2024)
BACKGROUND. At the beginning of the 21st century, the structure of acute exotoxicoses changed, in particular, an increase in poisoning by drugs that mainly affect the cardiovascular system, including calcium channel blockers, was noted. Currently, there is no clear treatment algorithm for this group of patients.   AIM OF STUDY. To evaluate the effectiveness of methods for the treatment of acute calcium channel blocker (ССВ) poisoning according to the literature.   MATERIAL AND METHODS. The search for domestic publications was carried out in the eLibrary database, foreign ones - in the MEDLINE/PubMed, Google Scholar databases for the period from 2010 to February 2022, as well as among previously published works that have no modern analogues. The terms used as a search query were according to the official MeSH terms: “calcium channel blockers” OR “Blockers, Calcium Channel” OR “Calcium Channel Antagonists” AND “poisoning”.   RESULTS. This review contains information about the mechanism of action, clinical picture, diagnosis of calcium channel blocker poisoning, as well as the results of using various methods of treatment for this pathology.   CONCLUSIONS. Summarizing the data obtained, it is possible to schematically present an algorithm for the treatment of patients with acute CCB poisoning. After cleansing the gastrointestinal tract and starting infusion therapy, pathogenetic treatment with the use of calcium preparations should be carried out, subsequently, in case of unstable hemodynamics, the prescription of vasopressors and inotropic drugs is indicated; and if there is no positive dynamics, insulin therapy must be added. However, it should be noted that such a scheme is indicative, reflecting the key points. In general, this problem remains open and requires further multicenter studies.